Cover Image. Issue 4 (5th March 2020) - Liao, Nien‐Chieh; Shih, Yung‐Luen; Ho, Ming‐Tak; Lu, Tai‐Jung; Lee, Ching‐Hsiao; Peng, Shu‐Fen; Leu, Sy‐Jye; Chung, Jing‐Gung
Abstract : The cover image is based on the Research Article Cardamonin induces immune responses and enhances survival rate in WEHI‐3 cell‐generated mouse leukemia in vivo by Nien‐Chieh Liao et al., https://doi.org/10.1002/tox.22881 .